Ca2+/Cation Antiporters (CaCA): Identification, Characterization and Expression Profiling in Bread Wheat (Triticum aestivum L.) - Taneja, Mehak; Tyagi, Shivi; Sharma, Shailesh; Upadhyay, Santosh Kumar (Frontiers in Plant Science, 2016)
The Ca2+/cation antiporters (CaCA) superfamily proteins play vital function in Ca2+ ion homeostasis, which is an important event during development and defense response. Molecular characterization of these proteins has been performed in certain plants, but they are still not characterized in Triticum aestivum (bread wheat). Herein, we identified thirty four TaCaCA superfamily proteins, which were classified into TaCAX, TaCCX, TaNCL and TaMHX protein families based on their structural organization and evolutionary relation with earlier reported proteins. Since the T. aestivum comprises an allohexaploid genome, TaCaCA genes were derived from each A, B and D subgenome and homeologous chromosome (HC), except chromosome-group 1. Majority of genes were derived from more than one HCs in each family that were considered as homeologous genes (HGs) due to their high similarity with each other. These HGs showed comparable gene and protein structures in terms of exon/intron organization and domain architecture. Majority of TaCaCA proteins comprised two Na_Ca_ex domains. However, TaNCLs consisted of an additional EF-hand domain with calcium binding motifs. Each TaCaCA protein family consisted of about ten transmembrane and two α-repeat regions with specifically conserved signature motifs except TaNCL, which had single α-repeat. Variable expression of most of the TaCaCA genes during various developmental stages suggested their specified role in development. However, constitutively high expression of a few genes like TaCAX1-A and TaNCL1-B indicated their role throughout the plant growth and development. The modulated expression of certain genes during biotic (fungal infections) and abiotic stresses (heat, drought, salt) suggested their role in stress response. Majority of TaCCX and TaNCL family genes were found highly affected during various abiotic stresses. However the role of individual gene needs to be established. The present study unfolded the opportunity for detail functional characterization of TaCaCA proteins and their utilization in future crop improvement programs.